Use of a robust alternative communication system in autism spectrum disorder: a case report - Ana Cristina de Albuquerque Montenegro; Letícia Karine Silvestre de Melo Silva; Renata Costa de Sá Bonotto; Rafaella Asfora Siqueira Campos Lima; Ivana Arrais de Lavor Navarro Xavier (Revista CEFAC, 2022)
ABSTRACT This study aimed at investigating the impact of using a robust augmentative and alternative communication (AAC) system on the communication of a child with autism spectrum disorder. This longitudinal intervention research is a single case study. Skills were assessed with data obtained with the protocol Communication Assessment in Autism Spectrum Disorder at the beginning and end of the intervention. Receptive and expressive communication and behavioral skills increased respectively by 62.5%, 36.84%, and 55.53%. Hence, positive results were found in communication development using the robust AAC system in the intervention, as verified in the progress in receptive and expressive communication and behavioral skills.